Chinese young consumers' brand loyalty toward sportswear products: a perspective of self-congruity. Issue 4 (20th July 2015) - Lu, Jinzhao; Xu, Yingjiao
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This study aims to investigate Chinese young consumers' brand loyalty toward sportswear products from a self-congruity perspective. With different performance observed between global and domestic sportswear brands in the Chinese market, this study also aims to examine the impact of country of origin on Chinese young consumers' behavior toward sportswear brands. Design/methodology/approach – A survey with street intercept method was conducted in Shanghai to collect data for this study. Multiple independent t-tests and structural equation modeling (SEM) with bootstrap method were used to test the hypotheses. Findings – The SEM results indicate a significant influence of brand self-congruity on consumers' brand association and perceived quality, which, in turn, influenced consumers' brand loyalty. The multiple t-test results suggest a significant difference between Chinese and global sportswear brands in terms of consumers' brand association and attitudinal brand loyalty. No significant difference was found in terms of consumers' behavioral brand loyalty. Research limitations/implications – The main limitation of this study comes from the convenience student sample. Practical implications – First, brands need to strategically design the brand image to represent the largest segment of the target market. Second, while global brands could focus on their pricing strategies, domestic brands need to focus more on maintaining a positive brand association in consumers' mind. Originality/value – This study contributes to the growing research on the self-congruity perspective of brand loyalty by empirically confirming the indirect effect of brand self-congruity on brand loyalty via the mediation effects of brand association and perceived quality in the context of the ever-growing Chinese sportswear market.